Mapping Social Behaviour of Suku Laut Communities in Traditional Coastal Settlements Landscape Element on Mainland Batam - Suwarlan, Stivani Ayuning; Lai, Lee Yoke; Said, Ismail; Nursyamsu, lathifa (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2024)
Sustainable future development is expected to support the creation of human welfare throughout the world, including traditional tribes and minorities. This research examines the phenomenon of a traditional tribe, namely the Sea Tribe or Suku Laut, which represents maritime communities on the mainland of Batam, Riau Islands, Indonesia, which requires special attention in the midst of industrial development and modernisation which has an impact on the sustainability of Suku Laut traditional coastal settlements. This research utilizes participant observation methods to analyze the social behaviour map of the Suku Laut community. This study found that community behaviour maps influence spatial formation and settlement patterns. In conclusion, social behaviour mapping provides benefits for the government in planning and managing traditional coastal settlements on the Batam mainland for future development in accordance with the social behaviour and local wisdom of the Suku Laut community.